VE-CoAP: A constrained application layer protocol for IoT video transmission. (1st January 2021) - Ghotbou, Arvin; Khansari, Mohammad
Abstract: Regarding the advantages of video for communications, it is expected that video transmission becomes an inseparable part of most IoT solutions which raises numerous challenges especially over LLNs (Low Power Lossy Networks). Considering these challenges and video transmission requirements for IoT applications, utilizing a proper application layer protocol plays an important role consequently. In this paper, a new application layer protocol for IoT video transmission scenarios, named VE-CoAP is proposed. VE-CoAP, which is an extended version of CoAP, develops complementary methods for improving CoAP performance and overcoming its challenges for video transmission scenarios especially over IoT and LLNs. These methods include pushing data from server to client, supporting parallel flows for data transmission as well as preserving video quality with a combination of guaranteed and best-effort transmission and also a ULP (Unequal Loss Protection) method for prioritizing data partitioned H.264 video sequence. To compare the performance of VE-CoAP to CoAP and HTTP, an evaluation considering metrics such as PSNR, SSIM and video delivery duration is performed. The evaluation shows that VE-CoAP outperforms its rivals for burst data transmission in both lossy or low loss networks and it also preserves video quality at a superior level compared to other protocols over LLNs.